The Inorganic Side of NGF: Copper(II) and Zinc(II) Affect the NGF Mimicking Signaling of the N-Terminus Peptides Encompassing the Recognition Domain of TrkA Receptor - Pandini, Giuseppe; Satriano, Cristina; Pietropaolo, Adriana; Gianì, Fiorenza; Travaglia, Alessio; La Mendola, Diego; Nicoletti, Vincenzo G.; Rizzarelli, Enrico (Frontiers in Neuroscience, 2016)
The nerve growth factor (NGF) N-terminus peptide, NGF(1-14), and its acetylated form, Ac-NGF(1-14), were investigated to scrutinise the ability of this neurotrophin domain to mimic the whole protein. Theoretical calculations demonstrated that non-covalent forces assist the molecular recognition of TrkA receptor for both peptides. Combined parallel tempering/docking simulations discriminated the effect of the N-terminal acetylation on the recognition of NGF(1-14) towards the domain 5 of TrkA (TrkA-D5). Experimental findings demonstrated that both NGF(1-14) and Ac-NGF(1-14) activate TrkA signaling pathways essential for neuronal survival. The NGF-induced TrkA internalization was slightly inhibited in the presence of Cu2+ and Zn2+ ions, whereas the metal ions elicited the NGF(1-14)-induced internalization of TrkA and no significant differences were found in the weak Ac-NGF(1-14)-induced receptor internalization. The crucial role of the metals was confirmed by experiments with the metal-chelator bathocuproine disulfonic acid, which discriminated different levels of inhibitory effects in the signalling cascade, due to different metal affinity of NGF, the free amino and the acetylated peptides. The NGF signaling cascade, activated by NGF (1−14) and Ac-NGF(1-14), induced CREB phosphorylation, but the copper addition further stimulated the Akt, ERK and CREB phosphorylation only for NGF and NGF(1-14). A dynamic and quick influx of both peptides into PC12 cells was tracked by live cell imaging with confocal microscopy. A significant role of copper ions was found in the modulation of peptide sub-cellular localization, especially at the nuclear level. Furthermore, a strong copper ionophoric ability of NGF(1-14) was measured. The Ac-NGF(1-14) peptide, which binds copper ions with a lower stability constant than NGF(1-14), exhibited a lower nuclear localization with respect to the total cellular uptake. These findings were correlated to the metal-induced increase of CREB and BDNF expression upon NGF(1-14) stimulation. In summary, we here validate NGF(1-14) and Ac-NGF(1-14) as first examples of monomer and linear peptides able to activate the NGF-TrkA signaling cascade. Metal ions modulate the activity of both NGF protein and the NGF-mimicking peptides. Such findings demonstrate that NGF(1-14) sequence can reproduce the signal transduction of whole protein, therefore represent a very promising drug candidate for further preclinical studies.